2001
DOI: 10.1034/j.1399-6576.2001.045004441.x
|View full text |Cite
|
Sign up to set email alerts
|

No effect of L‐arginine supplementation on pulmonary endothelial dysfunction after cardiopulmonary bypass

Abstract: In the current study L-arginine had no protective effect on the pulmonary endothelium after cardiopulmonary bypass, measured as reactivity to an infusion of acetylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Thus, drugs administered via systemic circulation might not effectively enter the lung parenchyma. This might partly explain the negative effect of L-arginine on pulmonary endothelial dysfunction after CPB when administrated systemically in a previous report [12].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Thus, drugs administered via systemic circulation might not effectively enter the lung parenchyma. This might partly explain the negative effect of L-arginine on pulmonary endothelial dysfunction after CPB when administrated systemically in a previous report [12].…”
Section: Discussionmentioning
confidence: 94%
“…However, the benefit of L-arginine in post-CPB lung injury prevention remains controversial [7,11,12]. Angdin et al found no effect of L-arginine on pulmonary endothelial dysfunction after CPB in a group of 35 adult patients [12]. In contrast, Yang et al showed that L-arginine infusion improved pulmonary surfactant integrity after CPB in animal study [11].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations